Técnicas quirúrgicas en el manejo del embarazo ectópico - Pesantez Morales, Angie Mabel (Machala : Universidad Técnica de Machala, 2023)
INTRODUCTION: Ectopic pregnancy is considered one of the main obstetric emergencies that can occur in the first trimester of pregnancy. The location of ectopic pregnancy occurs in 95% of cases, in the fallopian tube, and 1% in the scar area of a previous Caesarea. OBJECTIVE: Determine surgical techniques used in the management of ectopic pregnancy METHODOLOGY: Extensive searches were conducted in academic and scientific databases, such as PubMed and Google Scholar, using search terms such as "ectopic pregnancy", "diagnosis", "management"". Articles published in indexed journals were selected between 2018 and 2023. DEVELOPMENT: Early and accurate diagnosis of ectopic pregnancy is crucial for effective management. In this sense, transvaginal ultrasound has become the main diagnostic tool, with high sensitivity and specificity. β-hCG levels can determine effective treatment options to successfully resolve an ectopic pregnancy. CONCLUSION: The management of ectopic pregnancy depends on the clinical presentation of the patient, being conservative, minimally invasive or invasive. Invasive methods are: laparotomy, laparotomy + bilateral salpingectomy or unilateral salpingo-oophorectomy; and among miniinvasives, we have: uterine artery embolization, intraamniotic injection of potassium chloride or methotrexate, Dilation and curettage by suction and tamponade with Foley balloon. The implementation of local methotrexate injection, guided by ultrasound, is a convenient alternative to treat uncomplicated ectopic pregnancy.
INTRODUCCIÓN: Se considera al embarazo ectópico, como una de las principales urgencias obstétricas que se pueden presentar en el primer trimestre de gestación. La ubicación del embarazo ectópico ocurre en la 95% de los casos, en la trompa de Falopio, y un 1% en el área de cicatriz de una cesárea previa. OBJETIVO: Determinar las técnicas quirúrgicas usadas en el manejo del embarazo ectópico METODOLOGÍA: Se llevó a cabo una búsqueda exhaustiva en bases de datos académicas y científicas, como PubMed y Google Scholar, utilizando términos de búsqueda como "embarazo ectópico", "diagnóstico", "manejo"". Se seleccionaron artículos publicados en revistas indexadas en el período comprendido entre 2018 y 2023. DESARROLLO: El diagnóstico temprano y preciso del embarazo ectópico es crucial para un manejo efectivo. En este sentido, la ecografía transvaginal se ha convertido en la principal herramienta diagnóstica, con una sensibilidad y especificidad altas. Los niveles de β-hCG pueden determinar opciones de tratamiento efectivas para resolver con éxito un embarazo ectópico. CONCLUSIÓN: El manejo del embarazo ectópico depende de la presentación clínica del paciente, pudiendo ser conservador, mínimamente invasiva o invasiva. Los métodos invasivos son: laparotomía, laparotomía + salpingectomía bilateral o salpingooforectomía unilateral; y entre los miniinvasivos, tenemos: la embolización de arteria uterina, Inyección intraamniótica de cloruro de potasio o metotrexate, Dilatación y curetaje por succión y taponamiento con balón de Foley. La implementación de la inyección local de metotrexato, guiada por ecografía, es una alternativa conveniente para tratar el embarazo ectópico no complicado.
Keywords: EMBARAZO ECTÓPICO; EMBARAZO EXTRAUTERINO; DIAGNÓSTICO; MANEJO